The use of google sites in civic education learning in the Covid-19 pandemic era - Permatasari, Mitra; Murdiono, Mukhamad; Puspitasari, Chandra Dewi (Universitas Negeri Yogyakarta, 2022)
The Covid-19 pandemic has had an impact on the world of education and requires online learning in the learning process, especially in Civic Education. The purpose of this study is to describe the planning and organization of the use of google sites in Civics learning, strategies for using google sites, as well as the implementation and evaluation of the use of Google sites. This study uses a qualitative descriptive research method. Data collection techniques are interviews, observations, and documentation during the learning process. The results showed that the use of google sites in Civics learning in the Covid-19 pandemic era included planning and organizing by designing steps or stages to achieve goals. Then the strategy for using Google sites is to develop online learning media in the Covid-19 pandemic era by utilizing digital-based multimedia technology. Furthermore, the implementation and evaluation of the use of google sites is the interaction between lecturers and students online on google sites such as observing, asking, exploring, associating, and communicating activities. The use of google sites in online Civics learning in the Covid-19 pandemic era can be an effective and efficient learning media, using Google sites as an alternative media lecturers can use in learning activities in the Covid-19 pandemic era. Online learning on civic education uses google sites where students tend to be more active in discussions.